ANALISIS KREATIVITAS SISWA KELAS 3 DALAM MENGELOLA SAMPAH PLASTIK PADA PELAJARAN PLH DI SD NEGERI 1 WONOKROMO KECAMATAN GONDANG - Dessy Ayu Permata Hadi; Rohmatus Syafi’ah (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The Creativity is very needed to manage plastic waste become something new and can be re-used, because in Wonokromo district at Tulungagung was still many plastics waste that wasted and just fired, finally can be caused air-polution. The purpose of this research to know there is any creativity from students to manage plastic waste to be creative product that have a new value. Creative product that resulted from students at class 3 at SDN 1 Wonokromo valued with three criterias, it is: newness, fission, and detailed. Data collection methods that used is observation, interview, and documentation. The instrument that used is observation with ratting scale in create a data, and also use data of interview and documentation to support a data that a result of researcher. From this analysis data that result show that there is any creativity of students in class 3 at SDN 1 Wonokromo is very good because from fourteen students only one student that have a good criteria. The higher presentation is 94% and the lower is 68%.Keywords: creativity, creative products, plastic waste